RED BLOOD CELL TRANSFUSION IN PATIENTS WITH PLACENTA ACCRETA SPECTRUM: A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Placenta accreta spectrum (PAS) is associated with high maternal morbidity and mortality, mostly due to postpartum haemorrhage caused by aberrant placental-myometrial separation. In many instances of PAS, haemorrhage necessitates blood transfusion. Objective: To assess the utilisation of red blood cells in patients diagnosed with placenta accreta spectrum during the process of childbirth. Methods: A systematic review of literature published between 2003 and August 3, 2023 was performed across several databases including PubMed, Cochrane Library, and Google Scholar. Duplicate publications, review articles, and incomplete articles were excluded. Results: The databases search identified a total of 13,613 articles (Table 1) and resulted in 13,500 articles after duplicates removed. Of these, 13,420 articles were excluded due to non-original study and titles and abstract not represented the focus of interest; and resulting in 80 articles for screening process. Articles not evaluating the focus of interest and articles in which full-text are not available are excluded, resulting in 25 articles for evaluation of eligibility criteria. Among them, 21 articles given were not specified for RBCs transfusion and did not give sufficient details. Hence, we found 4 appropriate studies included Conclusion: Based on the studies included in this review, we are unable to recommend the minimum of units of red blood cells that should be available before delivery for patients with placenta accreta spectrum. Future studies in the form of large clinical trials is required to study the minimum of RBCs units for PAS patients before delivery, to better inform future guidelines for predelivery blood ordering and transfusion support.